First record of vocal mimicry in scarlet-headed blackbird amblyramphus holosericeus (Aves: Passeriformes) in the southeastern Brazil - Sementili-Cardoso, Guilherme [UNESP]; Marcelino, Raphael Sabongi Lúcio [UNESP]; Donatelli, Reginaldo José [UNESP] (Oecologia Australis, 2019)
Vocal mimicry is the ability of some bird species to copy heterospecific vocalizations in order to establish deceptive or non-deceptive interactions between an emitter and a receiver. This kind of vocal behavior is well documented in several species of New World Blackbirds (Icteridae family), but not in Scarlet-headed Blackbird (Amblyramphus holosericeus). Here we report the first event of vocal mimicry of this species, where a single individual imitated the vocal signals of Smooth-billed Ani (Crotophaga ani; Cuculiformes, Cuculidae). We argue that such behavior could have a deceptive role, increasing the predation avoidance and foraging efficiency of A. holosericeus by luring heterospecific individuals to form a mixed-flock.
Keywords: Bioacoustics; Dilution effect; Neotropical birds; Vocal imitation; Wetlands